PONDERACIÓN DE PRINCIPIOS EN EL TÍTULO DE IMPUTACIÓN (FACTOR DE ATRIBUCIÓN) DAÑO ESPECIAL: ANÁLISIS DESDE EL ESQUEMA ALEXIANO Y EL ESQUEMA KANTIANO (2016)
The constitutionalization of law has brought the gradual “abandonment” of the rules as the only valid source for the resolution of specific situations (especially in the higher courts) accepting the principles and criteria above which meet when settling disputes; This paradigm shift has gestated problems such as incompatibility of principles in solving a particular case, whatever their open texture does not clearly define the scope thereof, which is why we have made use of the weighting as a suitable tool for determining the principle applicable in every situation in response to the mandates of the alleged higher standard.This paper aims to analyze a sentence, in which the principles identified in collision and through the balancing exercise is determined by a sense of failure in either direction as the dominant principle that is applicable to it.